Metalloregulation of Helicobacter pylori physiology and pathogenesis - Gaddy, Jennifer A.; Haley, Kathryn P. (Frontiers in Microbiology, 2015)
Helicobacter pylori is a Gram-negative spiral-shaped bacterium that colonizes over half of the world’s population. Chronic H. pylori infection is associated with increased risk for numerous disease outcomes including gastritis, dysplasia, neoplasia, B-cell lymphoma of mucosal-associated lymphoid tissue (MALT lymphoma), and invasive adenocarcinoma. The complex interactions that occur between pathogen and host are dynamic and exquisitely regulated, and the relationship between the H. pylori and its human host are no exception. To successfully colonize, and subsequently persist, within the human stomach H. pylori must temporally regulate numerous genes to ensure localization to the gastric lumen and coordinated expression of virulence factors to subvert the host’s innate and adaptive immune response. H. pylori achieves this precise gene regulation by sensing subtle environmental changes including host-mediated alterations in nutrient availability and responding with dramatic global changes in gene expression. Recent studies revealed that the presence or absence of numerous metal ions encountered in the lumen of the stomach, or within host tissues, including nickel, iron, copper and zinc, can influence regulatory networks to alter gene expression in H. pylori. These expression changes modulate the deployment of bacterial virulence factors that can ultimately influence disease outcome. In this review we will discuss the environmental stimuli that are detected by H. pylori as well as the trans regulatory elements, specifically the transcription regulators and transcription factors, that allow for these significant transcriptional shifts.